ANALISIS PENERAPAN MODEL PEMBELAJARAN TIME GAME TOURNAMENT (TGT) PADA MATA PELAJARAN IPA DI SDN 1 LIMBOTO KABUPATEN GORONTALO - Olvin Jafar; Abd. Hamid Isa; Yusraningsih Pongoliu (Jurnal Ilmu Pendidikan UMGo, 2025)
This research aims to describe the application of the Time Game Tournament (TGT) learning model in science subjects. This research uses qualitative methods with data collection techniques, namely observation, interviews and documentation from primary data sources and secondary data. The data was analyzed by means of data reduction, data presentation, and drawing conclusions. The research results show that the implementation of the TGT learning model at SDN 1 Limboto has been implemented well, although there are still weaknesses in its implementation. This can be seen from research indicators, namely presentations in class, teams, games, tournaments and team awards. Of the five indicators, there are two indicators whose implementation is weak, namely Class Presentation and Games, while the Team, Tournament and Team Awards indicators have been implemented effectively. However, overall the implementation of the TGT model at SDN 1 Limboto has been implemented in facilitating the process and results in science learning. Based on this research, further research is recommended involving more participants and variations in the application of learning models.